The impact of europeanisation of criminal environmental protection on criminal law in the Czech Republic (Ius Novum, 2024)
The article focuses on the influence of the EU legal instruments on the criminal law of the Czech Republic in the field of environmental protection. The aim of the article is to analyse this influence and individual legal definitions of environmental crimes in the Czech legal system. For this purpose, the descriptive, comparative, analytical and logical methods are used. The author first assesses the state of environmental protection in the Czech Republic, not only by way of criminal law. This is followed by a list of legal definitions of individual criminal offences, and basic features and specific differences are explained for each of them with reference to the specific EU or public international law regulations on the basis of which the offence was introduced into the Czech legal system. The article also presents recent case law of the Supreme Court and the Constitutional Court of the Czech Republic concerning the issue. In the conclusions, the author assesses the level of environmental protection through criminal law and states that the Czech Republic is active in this area and fulfils its obligations resulting from the European regulations governing environmental protection.
Keywords: environmental protection, criminal law, European Union, Czech Republic, facts